2023
DOI: 10.1371/journal.pgen.1010582
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed fatty-acid metabolism is linked to localized chromatin hyperacetylation, increased stress-response gene expression and resistance to oxidative stress

Abstract: Oxidative stress is associated with cardiovascular and neurodegenerative diseases, diabetes, cancer, psychiatric disorders and aging. In order to counteract, eliminate and/or adapt to the sources of stress, cells possess elaborate stress-response mechanisms, which also operate at the level of regulating transcription. Interestingly, it is becoming apparent that the metabolic state of the cell and certain metabolites can directly control the epigenetic information and gene expression. In the fission yeast Schiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Cells lacking the cbf11 and/or mga2 gene display similar, non-additive growth and cellular defects Deletion of the cbf11 or mga2 transcription factor gene leads to impaired growth (Burr et al, 2016;Převorovský et al, 2009). Moreover, we have recently shown that both Δcbf11 and Δmga2 mutants exhibit increased expression of stress genes and are resistant to H2O2 (Princová et al, 2023). To investigate any potential genetic interactions between cbf11 and mga2, we first created Δcbf11 and Δmga2 single, and Δmga2 Δcbf11 double deletion strains in an isogenic background.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells lacking the cbf11 and/or mga2 gene display similar, non-additive growth and cellular defects Deletion of the cbf11 or mga2 transcription factor gene leads to impaired growth (Burr et al, 2016;Převorovský et al, 2009). Moreover, we have recently shown that both Δcbf11 and Δmga2 mutants exhibit increased expression of stress genes and are resistant to H2O2 (Princová et al, 2023). To investigate any potential genetic interactions between cbf11 and mga2, we first created Δcbf11 and Δmga2 single, and Δmga2 Δcbf11 double deletion strains in an isogenic background.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid as many confounding variables as possible, we used isogenic scarless TAP knock-in strains constructed using CRISPR/Cas9. The C-terminally tagged Cbf11-TAP strain has been described previously (Marešová et al, 2024; Princová et al, 2023). Inactive, membrane-bound Mga2 undergoes proteolytic activation that liberates its N-terminal part, which can then regulate transcription in the nucleus (Burr et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid biosynthesis itself has an intriguing function in activating stress responses. Compromised de novo fatty acid synthesis by mutation of fasn-1 enhanced the expression of anti-microbial genes in C. elegans 22 and oxidative stress response genes in yeast 28 . However, lipid biosynthesis by FASN-1 was shown to be required to initiate the mitochondria-to-cytosolic stress response triggering HSF-1 and DVE-1 transcriptional programs 29 .…”
Section: Discussionmentioning
confidence: 99%